MODEL PEMBELAJARAN SINTAKSIS DI PERGURUAN TINGGI DI JATENG DAN DIY - Markhamah, Markhamah; Ngalim, Abdul; Basri, Muhammad Muinudinillah; Mursiah, Tatik; Prasetyo, Ari; Prasetyo, Thomas (Universitas Muhammadiyah Surakarta, 2012)
A research on Syntax learning model in university is needed because such research is barely available for reference yet. Existing research on learning models are commonly carried out in high and middle schools, not university. This research aims to expose Syntax learning model in universities in Central Java and Yogyakarta.As object of research, two departments of Indonesian Language and Literature in Yogyakarta, one department of Indonesian language and Literature in Central Java, and one department of Indonesian Language and Literature Education in Central Java are chosen to be analyzed. The model includes: existence of lecture plan (RPP/RMP), teaching material, lecturer methods/strategy, learning media, and evaluation method. Data of research is collected through interview and document analysis, which is done quantitatively us- ing interactive and comparative models. This research reaches five conclusions. First, all departments in the research have both RPP (lecture plan) and RMP (lecture quality plan), even though with slight differences in names and details. Second, the departments have similarities and differences in term of teaching material. As a similarity, teaching material based on lecturer research is not found. Third, the departments have similarities and differences in term of teaching methods. Interestingly, some departments use unique learning method that synergizes with ideology of the particular university. Fourth, learning media between the departments is varied. Not every department is familiar with multimedia technology though some lecturers smartly use games as learning media to cover the lack of multimedia technology. Fifth, the departments use different evaluation method with different components. Some departments uses UKD (base competence test) while some are using UAS (end semester test).